(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article examines key medical and social aspects of increasing birth rates. It analyzes the main factors affecting female fertility, including age, hormonal balance, ovulation, lifestyle, and chronic diseases. Modern methods to improve reproductive health, such as hormonal therapy, surgical interventions, and assisted reproductive technologies (ART), are discussed. Special attention is given to the role of psychological well-being and infertility prevention.